EDUCATION IN THE CITY OF BAGHDAD BETWEEN THE PAST AND THE PRESENT (International Journal of Engineering Sciences & Management Research, 2020)
The Iraq has witnessed the manifestations of the cradle of the first letter, as its civilization is very ancient, and it is not surprising that the achievements spread in its territories, and it has left clear fingerprints on the face of history because its civilization was not marginal or emergent, that was appearing at one time and was disappearing at another time, as it is an ancient land with the antiquity of time, and is still engraved in memory time is its eternal eternity, and Baghdad is associated with the cities of Sapar and Kish, where two schools dating back to the era of Hammurabi in the period (539-526 BC) were found and the schools were then called (House of Panels).